2015
DOI: 10.1021/acs.est.5b03413
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm Uptake Routes and Rates of Ionic Zn and ZnO Nanoparticles at Realistic Concentrations, Traced Using Stable Isotope Labeling

Abstract: The environmental behavior of ZnO nanoparticles (NPs), their availability to, uptake pathways by, and biokinetics in the earthworm Lumbricus rubellus were investigated using stable isotope labeling. Zinc isotopically enriched to 99.5% in (68)Zn ((68)Zn-E) was used to prepare (68)ZnO NPs and a dissolved phase of (68)Zn for comparison. These materials enabled tracing of environmentally relevant (below background) NP additions to soil of only 5 mg (68)Zn-E kg(-1). Uptake routes were isolated by introducing earthw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…[27][28][29] The stable isotope labeling method has been used to detect the toxicity and bioaccumulation of several types of NPs with high sensitivity and reliability. 27,28,[30][31][32][33][34] In this study, we synthesized isotopically AgNO 3 and 3.7 mL of 34 mmol L −1 trisodium citrate dihydrate were added into 100 mL of boiling distilled water, and then 1 mL of 50 mmol L −1 sodium borohydride was added drop-wise into the solution with vigorous stirring. The solution turned from colorless to yellow immediately, and the color deepened with further addition of sodium borohydride.…”
Section: -5mentioning
confidence: 99%
“…[27][28][29] The stable isotope labeling method has been used to detect the toxicity and bioaccumulation of several types of NPs with high sensitivity and reliability. 27,28,[30][31][32][33][34] In this study, we synthesized isotopically AgNO 3 and 3.7 mL of 34 mmol L −1 trisodium citrate dihydrate were added into 100 mL of boiling distilled water, and then 1 mL of 50 mmol L −1 sodium borohydride was added drop-wise into the solution with vigorous stirring. The solution turned from colorless to yellow immediately, and the color deepened with further addition of sodium borohydride.…”
Section: -5mentioning
confidence: 99%
“…22,23 These labelled NPs enhance the signal to noise ratio of the NP from the background element by measuring the ratio of the enriched isotope against a non-enriched (background) isotope. This has allowed for a significant reduction in detection limits within organisms by up to two orders of magnitude.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…After the QDs were added to these media, all of the samples were agitated and then acidified to obtain 2% of nitric acid in the samples (in the case of the blood plasma samples, 1.5% of hydrochloric acid was used as complete digestion was not reached using nitric acid), and then left overnight prior to dilution and analysis. This acidification step is representative of the final step used in many studies prior to ENP analysis 15,19 . Simple acidification was sufficient to completely dissolve the QDs, and therefore complete acid digestion with HF/HNO 3 was not carried out.…”
Section: Methodsmentioning
confidence: 99%
“…2 open trace the QDs and to understand their behavior in biological environments at low concentrations (ppt-ppb level). In fact, isotopically labelled nanoparticles (NPs) are increasingly being used in the literature to better quantify manufactured NPs in biological matrices [15][16][17][18][19] . For instance, Khan et al showed the ability to conduct environmentally relevant exposures (20 µg 68 Zn/L) of spiked ZnO NPs in order to study their bioavailability to estuarine snails, whereas Bourgeault et al provided evidence for the critical use of spiked 47 TiO 2 NPs when studying the bioaccumulation of NPs at environmental concentrations (7-120 µg/L of 47 TiO 2 NPs) in zebra mussels in water.…”
mentioning
confidence: 99%